A Stochastic Sequencing Problem for Style Goods with Forecast Revisions and Hierarchical Structure - Matsuo, Hirofumi (Management Science, 1990)
This paper addresses the problem of simultaneously determining a production sequence and production volumes of style goods. Style goods have one selling season per year. During the rest of the year, manufacturers of style goods build up the inventory while continuously reestimating the demand in the final selling season. In this problem, products have a two-stage hierarchy: items and families. The production of a family is assumed to be nonpreemptive. Exploiting the hierarchical structure, we formulate the problem as a two-stage stochastic sequencing problem: the stochastic aggregate sequencing problem and the stochastic disaggregation problem. To solve the stochastic aggregate sequencing problem, a simple heuristic solution procedure is developed that accounts for the forecast revisions and provides a lower bound on the optimal value. The heuristic is tested using the disguised data obtained from a consumer electronics company. The computational results demonstrate the applicability of the proposed procedure.